2020
DOI: 10.1016/s2214-109x(20)30261-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survival and survival gap apportionment in sub-Saharan Africa (ABC-DO): a prospective cohort study

Abstract: Background Breast cancer is the second leading cause of death from cancer in women in sub-Saharan Africa, yet there are few well characterised large-scale survival studies with complete follow-up data. We aimed to provide robust survival estimates in women in this setting and apportion the survival gaps.Methods The African Breast Cancer-Disparities in Outcomes (ABC-DO) prospective cohort study was done at eight hospitals across five sub-Saharan African countries (Namibia, Nigeria, South Africa, Uganda, and Zam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
164
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 26 publications
8
164
0
8
Order By: Relevance
“…Yet, despite this baseline poor prognosis among the general breast cancer population, this meta-analysis showed that WLWH in Sub-Saharan Africa do even worse in terms of survival compared to HIV-negative Sub-Saharan African women, despite adjustment for age, stage and subtype. This has been recently confirmed by the survival analysis of the ABC-DO study, showing that age-stage adjusted HR for 3-year all-cause mortality was 1.48 (95% CI, 1.22-1.81) among WLWH compared to HIV-negative women, which is similar to our findings [48].…”
Section: Discussionsupporting
confidence: 91%
“…Yet, despite this baseline poor prognosis among the general breast cancer population, this meta-analysis showed that WLWH in Sub-Saharan Africa do even worse in terms of survival compared to HIV-negative Sub-Saharan African women, despite adjustment for age, stage and subtype. This has been recently confirmed by the survival analysis of the ABC-DO study, showing that age-stage adjusted HR for 3-year all-cause mortality was 1.48 (95% CI, 1.22-1.81) among WLWH compared to HIV-negative women, which is similar to our findings [48].…”
Section: Discussionsupporting
confidence: 91%
“…Because organized, population‐based mammography screening programs may not be cost effective or feasible in low‐resource settings, 50 efforts to promote early detection through improved breast cancer awareness and clinical breast examination by skilled health providers, 51,52 followed by timely and appropriate treatment, are essential components to improving survival 53 . A recent study conducted in 5 sub‐Saharan African countries estimated that 28% to 37% of breast cancer deaths in these countries could be prevented through earlier diagnosis of symptomatic disease and adequate treatment, with a fairly equal contribution of each 54 . The Breast Health Global Initiative has established a series of evidence‐based, resource‐stratified guidelines that supports phased implementation into real‐world practice 55‐57 …”
Section: Resultsmentioning
confidence: 99%
“…The number of maternal orphans was associated with maternal deaths in women younger than 50 years, and owing to higher fertility levels, particularly affected HIV-negative women and women in rural communities. Lower socioeconomic groups, which have lower breast cancer survival, 5 result in more maternal orphans, thus propagating a cycle of disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although half (48%) of these deaths occur in women younger than 50 years (eFigure in the Supplement), we are not aware of quantifications of the resulting maternal orphans. In the present study, we examined these numbers in the African Breast Cancer-Disparities in Outcomes (ABC-DO) cohort 4,5 and highlight the outcomes of the deaths in families.…”
mentioning
confidence: 99%